Determination Analysis Of Coastal and Small Islands Conservation Area Jailolo Bay Using The Marxan Method - Ahmad, Aditiyawan; Wahidin, Nurhalis (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Jailolo Bay conditions for utilization activities, in the long term can cause conflicts of use, therefore it is necessary to regulate the utilization according to its designation with a zoning approach so as to prevent conflicts that will occur. The purpose of this study is to determine the zoning of the use of Jailolo Bay as a coastal conservation area and small islands using the Marxan method. Based on the analysis of the factors that support the determination of Coastal and Small Islands Conservation Areas in the waters of Jailolo Bay, the main recommendation is Coastal Park and the alternative recommendation is Coastal Sanctuary. The area of the coastal and small islands conservation area of Jailolo Bay is 1,166.46 ha, consisting of a core zone of 23.50 ha, a utilization zone of 43.75 ha, a sustainable fisheries zone of 1,084.86 ha, and other zones of 14.35 ha.